Gut Microbiota Composition and Metabolic Potential of Long-Living People in China - Zhang, Siyuan; Ning, Ruihong; Zeng, Bo; Deng, Feilong; Kong, Fanli; Guo, Wei; Zhao, Jiangchao; Li, Ying (Frontiers in Aging Neuroscience, 2022)
Individuals with naturally long life spans have been extensively studied to gain a greater understanding of what factors contribute to their overall health and ability to delay or avoid certain diseases. Our previous work showed that gut microbiota can be a new avenue in healthy aging studies. In the present study, a total of 86 Chinese individuals were assigned into three groups: long-living group (90+ years old; n=28), elderly group (65-75 years old; n=31) and young group (24-48 years old; n=27). These were used to explore the composition and functional genes in the microbiota community by using the metagenomic sequencing method. We found that long-living individuals maintained high diversity in gene composition and functional profiles. Furthermore, their microbiota displays less inter-individual variation than that of the elderly adults. In the taxonomic composition, it was shown that long-living people contained more short chain fatty acid (SCFA)-producing bacteria, and a decrease in certain pathogenic bacteria. Functional analysis also showed that the long-living people were enriched in metabolism metabolites methanol, trimethylamine (TMA) and CO2 to methane, and lysine biosynthesis, but the genes related to riboflavin (vitamin B2) metabolism and tryptophan biosynthesis were significantly reduced in long-living individuals. Further, we found that long-living people with enriched SCFA- and lactic-producing bacteria and related genes, highly center on producing key lactic acid genes (ldhA) as well as the genes of lysine that are metabolized to the butyrate pathway. In addition, we compared the gut microbiota signatures of longevity in different regions and found that the composition of the gut microbiota of the long-lived Chinese and Italian people was quite different, but both groups were enriched in genes related to methane production and glucose metabolism. In terms of SCFA metabolism, the Chinese long-living people were enriched with bacteria and genes related to butyric acid production, while the Italian long-living people were enriched with more acetic acid-related genes. These findings suggest that the gut microbiota of Chinese long-living individuals include more SCFA-producing bacteria and genes, metabolizes methanol, TMA and CO2, and contains fewer pathogenic bacteria, thereby potentially contributing to the healthy aging of humans.